2010
DOI: 10.1111/j.1476-5381.2009.00476.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of GPCR structures on pharmacology and structure‐based drug design

Abstract: After many years of effort, recent technical breakthroughs have enabled the X-ray crystal structures of three G-protein-coupled receptors (GPCRs) (b1 and b2 adrenergic and adenosine A2a) to be solved in addition to rhodopsin. GPCRs, like other membrane proteins, have lagged behind soluble drug targets such as kinases and proteases in the number of structures available and the level of understanding of these targets and their interaction with drugs. The availability of increasing numbers of structures of GPCRs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(95 citation statements)
references
References 97 publications
(109 reference statements)
4
91
0
Order By: Relevance
“…The results reported here are comparable to those from other similar works [19][20][21][22] which showed that GPCR modeling [23][24][25][26][27][28][29][30][31] in the absence of a crystal structure can be a valid replacement [32][33][34][35][36][37][38][39] for structural and functional exploration of GPCR receptors, and for the discovery [21,[40][41][42][43], VS [44][45][46][47][48][49][50][51][52] and optimisation [23,53] of their ligands.…”
Section: Introductionsupporting
confidence: 80%
“…The results reported here are comparable to those from other similar works [19][20][21][22] which showed that GPCR modeling [23][24][25][26][27][28][29][30][31] in the absence of a crystal structure can be a valid replacement [32][33][34][35][36][37][38][39] for structural and functional exploration of GPCR receptors, and for the discovery [21,[40][41][42][43], VS [44][45][46][47][48][49][50][51][52] and optimisation [23,53] of their ligands.…”
Section: Introductionsupporting
confidence: 80%
“…These compounds represent a diversity of scaffolds common in drugs and drug candidates (e.g., heterocycles, piperazines, etc.) and most obey the "Rule of 3," which was established to judge fragments as suitable starting points for drug discovery efforts (mass <300 Da, predicted cLogP ≤3, number of hydrogen-bond donors/acceptors ≤3) (14). Preliminary experiments revealed that the disulfide fragments reacted much more readily with the PDK1 Cys mutants than did the Cys-PIFtides; at 100 μM β-ME and 100 μM compound, most small molecule disulfides reacted quantitatively with every Cys mutant.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, companies whose target portfolios are increasingly filled with GPCRs and ion channels will find this approach less tractable. While there has been tremendous recent success in the isolation and X-ray structural analysis of membrane proteins [19,20], routine application of FBDD to these targets is still some time away [21].…”
Section: Disease Area Focus and Strategymentioning
confidence: 99%